Effects of supplemental carnitine on nitrogen balance and blood metabolites of growing beef steers fed a high-protein, corn-based diet - Greenwood, R.H.; Stokka, Gerald L.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seven Angus-cross steers (475 lbs initial body weight) were used in a 7 × 4 incomplete Latin square experiment to evaluate the effects of supplemental L-carnitine on nitrogen balance and blood metabolites. Steers were fed the same high-protein, corn-based diet near ad libitum intake. Treatments were control and .25, .5, 1.0, 1.5, 2.0, and 3.0 grams/day of supplemental carnitine. Experimental periods were 18 days with 13 days for adaptation and 5 days for collection of feces and urine. Blood was collected at feeding and 3 and 6 hours after feeding on day 18 of each period. Supplementing steers with carnitine increased urinary carnitine excretion and plasma carnitine concentration. Nitrogen retention (a measure of protein deposition) was not affected by carnitine supplementation and averaged 29.3 g/d. Plasma insulin and glucagon, indicative of energy status, and cholesterol and triglyceride, representative of energy storage metabolites, were not affected by carnitine supplementation. Plasma glycerol and beta-hydroxybutyrate, reflective of fat catabolism, increased with intermediate levels of supplemental carnitine. In conclusion, carnitine supplementation did not alter N balance in our experiment, but it did alter some of the plasma metabolites of steers fed high-protein, corn-based diets.
Keywords: Beef; Growing steers; Carnitine; Nitrogen balance; Plasma metabolites